The relationship between problem behaviour and traumatic dental injury amongst children aged 7–15 years old - Odoi R, Croucher R, Wong F, Marcenes W. (Blackwell Synergy, 2002)
The aim of this study was to test whether dental injuries are related to problem behaviour. In addition, it aimed to confirm the relationship between dental injuries and size of overjet and type of lip coverage.